2023
DOI: 10.1080/22221751.2022.2164217
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of cell homeostasis and antiviral innate immunity by autophagy during classical swine fever virus infection

Abstract: CSFV (classical swine fever virus) is currently endemic in developing countries in Asia and has recently re-emerged in Japan. Under the pressure of natural selection pressure, CSFV keeps evolving to maintain its ecological niche in nature. CSFV has evolved mechanisms that induce immune depression, but its pathogenic mechanism is still unclear. In this study, using transcriptomics and metabolomics methods, we found that CSFV infection alters innate host immunity by activating the interferon pathway, inhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Our lab and a recent study have reported that the innate immune-associated molecules, RIG-I, could be degraded by autophagy [ 20 , 21 ]. Additionally, RIG-I is an important sensor for RNA viruses to trigger the interferon response.…”
Section: Resultsmentioning
confidence: 99%
“…Our lab and a recent study have reported that the innate immune-associated molecules, RIG-I, could be degraded by autophagy [ 20 , 21 ]. Additionally, RIG-I is an important sensor for RNA viruses to trigger the interferon response.…”
Section: Resultsmentioning
confidence: 99%
“…Many viruses, such as swine fever virus and porcine reproductive and respiratory virus, have activated the JAK3-STAT pathway to release cytokines. Although moderate levels of cytokines could stimulate host immune responses for protection, myriad cytokines destroy cell homeostasis and cause damage [ 51 , 52 ]; therefore, the significantly reduced gene expressions in the JAK3-STAT pathway might be a developed protective mechanism for WZS pigs. On the other hand, the upregulated expression of HSPD1 contributed to increased cell viability while reducing apoptosis and oxidative damage in H 2 O 2 -treated cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, autophagy maintains the health and functionality of the cell. 24 It also plays important roles in viral infections. HSV-1 induced the formation of autophagosomes in the infected macrophage, and the virus was engulfed in the autophagosomes and processed by the proteasome.…”
Section: Discussionmentioning
confidence: 99%